Chemically strengthened glass, crystallized glass, and methods for producing the same
A chemically strengthened glass with Li3PO4 and Li4SiO4 crystals addresses transparency and productivity issues in conventional crystallized glass, offering enhanced strength and thermal expansion properties.
Patent Information
- Application Number
- JP2023124433
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-05-28
- Filing Date
- 2023-07-31
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2041-08-10
AI Technical Summary
Conventional chemically strengthened crystallized glass often suffers from insufficient transparency and requires high heat treatment temperatures, affecting productivity.
A chemically strengthened glass composition containing Li3PO4 and Li4SiO4 crystals with specific ratios and heat treatment conditions, achieving a haze value of 0.5% or less and a tensile stress integral ST limit of 18,000 to 30,000 MPa·μm, while being produced at lower temperatures.
The solution provides glass with excellent transparency, strength, and a large coefficient of thermal expansion, suitable for applications requiring high durability and chemical resistance.
Smart Images

Figure 0007605259000012 
Figure 0007605259000013 
Figure 0007605259000014
Abstract
Description
[Technical field]
[0001] The present invention relates to crystallized glass and chemically strengthened glass, and to methods for producing the same. [Background technology]
[0002] Chemically strengthened glass is used for cover glass of mobile terminals, etc. Chemically strengthened glass is produced by contacting glass with a molten salt containing alkali metal ions, for example, to cause ion exchange between the alkali metal ions in the glass and the alkali metal ions in the molten salt, thereby forming a compressive stress layer on the glass surface.
[0003] Glass-ceramics is glass in which crystals have been precipitated, and is harder and less susceptible to damage than amorphous glass, which does not contain crystals. In addition, glass-ceramics that can be chemically strengthened have a larger CT limit than amorphous glass, making it possible to achieve high strength while preventing shattering. However, conventional glass-ceramics often lack transparency compared to amorphous glass.
[0004] The greater the compressive stress formed on the surface of chemically strengthened glass, the stronger it becomes, but inside the chemically strengthened glass, a tensile stress (CT) is generated that offsets the compressive stress. If the CT becomes too large, the chemically strengthened glass will shatter violently when it breaks. The maximum tensile stress value that can prevent violent shattering is called the CT limit.
[0005] Patent Document 1 describes an example in which crystallized glass is chemically strengthened by ion exchange treatment. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] International Publication No. 2019 / 022035 Summary of the Invention [Problem to be solved by the invention]
[0007] Although the crystallized glass described in Patent Document 1 has excellent transparency and chemical strengthening properties, the transparency may be insufficient. In addition, the heat treatment temperature required for melting the glass raw material and for crystallization is high, which raises concerns about productivity.
[0008] The present invention provides amorphous glass having excellent transparency and strength and a large thermal expansion coefficient, crystallized glass having excellent transparency and chemical strengthening properties, a large thermal expansion coefficient, and capable of being produced at a relatively low temperature, and chemically strengthened glass having excellent transparency, strength, and a large thermal expansion coefficient. [Means for solving the problem]
[0009] The present invention relates to a chemically strengthened glass, which is a crystallized glass having a haze value of 0.5% or less converted to a thickness of 0.7 mm, a surface compressive stress value of 400 MPa or more, a compressive stress layer depth of 70 μm or more, and an ST limit of 18,000 to 30,000 MPa·μm as determined by the following test method, and which contains at least one of Li3PO4 crystals and Li4SiO4 crystals, or a solid solution crystal of either Li3PO4 and Li4SiO4, or a solid solution of both. (Test Method) The test glass plates are 15 mm square and 0.7 mm thick with a mirror-finished surface, and are chemically strengthened under various conditions to prepare multiple test glass plates with different tensile stress integral values ST. Using a Vickers testing machine, a diamond indenter with a 90° tip angle is driven into the center of the test glass plate to break it, and the number of broken pieces is recorded as the number of broken pieces. The test is started with a diamond indenter driving load of 1 kgf, and if the glass plate does not break, the driving load is increased by 1 kgf and the test is repeated until the glass plate breaks, and the number of broken pieces at the first break is counted. The number of fractures is plotted against the ST value of the test glass plate, and the ST value at which the number of fractures is 10 is read and taken as the ST limit.
[0010] The present invention relates to a crystallized glass that contains at least one of Li3PO4 crystals and Li4SiO4 crystals, or a solid solution crystal of either Li3PO4 or Li4SiO4, or a solid solution of both, and that has a haze value of 0.5% or less when converted into a thickness of 0.7 mm, and a tensile stress integral value ST limit of 18,000 MPa·μm or more.
[0011] The present invention is expressed in mole percent based on oxides. SiO2 40-70%, Li2O 10~35%, Al2O3 1-15%, P2O5 0.5-5%, ZrO2 0.5-5%, B2O3 0-10%, Na2O 0-3%, K2O 0-1%, Contains 0-4% SnO2. The total amount of SiO2, Al2O3, P2O5 and B2O3 is 60-80%; The ratio of the total amount of Li2O, Na2O and K2O to the total amount of SiO2, Al2O3, P2O5 and B2O3 is 0.20 to 0.60, and the glass-ceramics contains Li3PO4 or Li4SiO4 as the main crystal.
[0012] The present invention is expressed in mole percent based on oxides. SiO2 40-70%, Li2O 10~35%, Al2O3 1-15%, P2O5 0.5-5%, ZrO2 0.5-5%, B2O3 0-10%, Na2O 0-3%, K2O 0-1%, Contains 0-4% SnO2. The total amount of SiO2, Al2O3, P2O5 and B2O3 is 60-80%; The present invention relates to a method for producing crystallized glass, in which a ratio of the total amount of Li2O, Na2O and K2O to the total amount of SiO2, Al2O3, P2O5 and B2O3 is 0.20 to 0.60, is subjected to a heat treatment at a temperature of 450°C or higher and 800°C or lower.
[0013] The present invention also provides a semiconductor support substrate made of the amorphous glass, crystallized glass, or chemically strengthened glass. Effect of the Invention
[0014] The present invention provides an amorphous glass having excellent transparency and strength and a large thermal expansion coefficient. It also provides a crystallized glass having excellent transparency and chemical strengthening properties and a large thermal expansion coefficient. It also provides a chemically strengthened glass having excellent transparency and strength and a large thermal expansion coefficient. [Brief description of the drawings]
[0015] [Figure 1] FIG. 1 shows the results of X-ray diffraction of glass-ceramics. [Diagram 2] FIG. 2 is a diagram showing a stress profile of chemically strengthened glass. [Diagram 3] Fig. 3 shows a cross-sectional FE-SEM image of the crystallized glass, in which the white arrows indicate examples of precipitated crystals. [Figure 4] FIG. 4 is an explanatory diagram of a sample used in measuring the fracture toughness value K1c by the DCDC method. [Diagram 5] FIG. 5 shows the K1-v curve, which shows the relationship between the stress intensity factor K1 (unit: MPa m1 / 2) and the crack propagation velocity v (unit: m / s), used in measuring the fracture toughness value K1c by the DCDC method. [Figure 6] 6A and 6B show a supporting glass according to one embodiment of the present invention to be bonded to a semiconductor substrate, in which FIG. 6A is a cross-sectional view before bonding and FIG. 6B is a cross-sectional view after bonding. [Figure 7] FIG. 7 shows a cross-sectional view of a laminated substrate according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] In this specification, unless otherwise specified, the use of "to" indicating a numerical range means that the numerical values before and after it are included as the lower limit and upper limit.
[0017] In this specification, "amorphous glass" refers to glass that does not show any diffraction peaks indicating crystals by the powder X-ray diffraction method described later. "Crystallized glass" is obtained by heating "amorphous glass" to precipitate crystals, and contains crystals. In this specification, "amorphous glass" and "crystallized glass" are sometimes collectively referred to as "glass." In addition, amorphous glass that becomes crystallized glass by heat treatment is sometimes referred to as "mother glass of crystallized glass."
[0018] In this specification, the powder X-ray diffraction measurement is performed by, for example, using CuKα radiation to measure the range of 2θ from 10° to 80°, and when a diffraction peak appears, the precipitated crystals are identified by the Hanawalt method. In addition, the crystals identified from the peak group including the peak with the highest integrated intensity among the crystals identified by this method are regarded as the main crystals. As a measuring device, for example, SmartLab manufactured by Rigaku Corporation can be used.
[0019] In the following, "chemically strengthened glass" refers to glass after chemical strengthening treatment, and "glass for chemical strengthening" refers to glass before chemical strengthening treatment.
[0020] In this specification, glass compositions are expressed in mol % based on oxides unless otherwise specified, and mol % is simply represented as "%".
[0021] In addition, in this specification, "substantially free" means that the content is below the impurity level contained in raw materials, that is, that it is not intentionally added. Specifically, for example, it is less than 0.1%.
[0022] In this specification, the term "stress profile" refers to a representation of compressive stress values with the depth from the glass surface as a variable. In the stress profile, tensile stress is represented as negative compressive stress.
[0023] The "compressive stress value (CS)" can be measured by cutting a cross section of glass into thin slices and analyzing the sliced samples with a birefringence imaging system. A birefringence imaging system birefringence stress meter is a device that measures the magnitude of retardation caused by stress using a polarizing microscope and a liquid crystal compensator, etc., and one example is the birefringence imaging system Abrio-IM manufactured by CRi.
[0024] Measurements can also be made using scattered light photoelasticity. With this method, light is incident on the glass surface, and the polarization of the scattered light is analyzed to measure CS. An example of a stress measuring device that uses scattered light photoelasticity is the SLP-2000 scattered light photoelasticity meter manufactured by Orihara Seisakusho.
[0025] In this specification, the "depth of compressive stress layer (DOL)" is the depth at which the compressive stress value becomes zero. In the following, the surface compressive stress value is CS0, and the compressive stress value at a depth of 50 μm is CS 50 Also, "internal tensile stress (CT)" refers to the tensile stress value at a depth of 1 / 2 the plate thickness t.
[0026] "Tensile stress integral (ST value)" refers to the area integral of tensile stress (negative compressive stress) for the sample depth from the DOL to a depth of 1 / 2 the plate thickness t. In chemically strengthened glass, when the ST value in the glass reaches a certain threshold or more, the number of fractures increases rapidly when the glass breaks. This threshold is called the "ST limit."
[0027] As used herein, the "ST limit" is measured by the following method. (ST limit measurement method) The test glass plates are 15 mm square and 0.7 mm thick, with a mirror-finished surface, and are chemically strengthened under various conditions to prepare a number of test glass plates with different ST values. Using a Vickers testing machine, a diamond indenter with a 90° tip angle is driven into the center of the test glass plate to break it, and the number of broken pieces is recorded as the number of broken pieces. The test is started with a diamond indenter driving load of 1 kgf, and if the glass plate does not break, the driving load is increased by 1 kgf and the test is repeated until the glass plate breaks, and the number of broken pieces at the first break is counted. The number of fractures is plotted against the ST value of the test glass plate, and the ST value at which the number of fractures is 10 is read and taken as the ST limit.
[0028] In this specification, "light transmittance" refers to the average transmittance of light with a wavelength of 380 nm to 780 nm. Furthermore, "haze value" is measured using a halogen lamp C light source in accordance with JIS K7136:2000.
[0029] In this specification, the "fracture toughness value Kc" is a value obtained by the IF method defined in JIS R1607:2015.
[0030] In this specification, the "fracture toughness value K1c" is measured by the DCDC method [Reference: MY He, MR Turner and AG Evans, Acta Metall. Mater. 43 (1995) 3453.]. Specifically, the stress intensity factor K1 (unit: MPa m) as shown in FIG. 5 was measured using a sample having the shape shown in FIG. 4 and a Shimadzu autograph AGS-X5KN. 1 / 2 The K1-v curve, which shows the relationship between the stress intensity factor K1 at 0.1 m / s and the crack propagation velocity v (unit: m / s), is measured, and the obtained Region III data is regressed and extrapolated using a linear equation, and the stress intensity factor K1 at 0.1 m / s is determined as the fracture toughness value K1c.
[0031] In this specification, the term "semiconductor" refers not only to a semiconductor wafer such as silicon or a semiconductor chip, but also to a composite including a chip, a wiring layer, and a molding resin.
[0032] In this specification, the crack initiation load (CIL) refers to the indentation load of a Vickers indenter with a tip angle of 136° that results in a 50% crack occurrence rate when an indentation is made on a mirror-finished surface having a thickness of 0.7 mm or more. (Method of measuring CIL) Prepare a 0.7mm thick plate-shaped glass with mirror polished on both sides. Using a Vickers hardness tester, press the Vickers indenter for 15 seconds, then remove the Vickers indenter, and observe how many cracks have appeared from the corners of the indentation after 15 seconds. Measurements are performed on 10 pieces of glass with Vickers indenter pressing loads of 10gf, 25gf, 50gf, 100gf, 200gf, 300gf, and 500gf, and the average number of cracks that have appeared is calculated for each load. The relationship between load and number of cracks is calculated by regression using a sigmoid function, and the load at which the number of cracks becomes two is defined as CIL (gf). The atmospheric conditions for the measurement are an air temperature of 25°C and a dew point of -40°C.
[0033] <Chemically strengthened glass> The chemically strengthened glass of the present invention (hereinafter also referred to as the present strengthened glass) is typically a plate-shaped glass product, and may be flat or curved. It may also have a portion with a different thickness. It is also a crystallized glass containing at least one of Li3PO4 crystals and Li4SiO4 crystals, or a solid solution crystal of either Li3PO4 and Li4SiO4, or both solid solutions. The crystallized glass containing at least one of Li3PO4 crystals and Li4SiO4 crystals, or a solid solution crystal of either Li3PO4 and Li4SiO4, or both solid solutions will be described later.
[0034] When the present chemically strengthened glass is in the form of a plate, the thickness (t) is preferably 3 mm or less, more preferably 2 mm or less, 1.6 mm or less, 1.1 mm or less, 0.9 mm or less, 0.8 mm or less, and 0.7 mm or less in the following stepwise manner. In addition, the thickness (t) is preferably 0.3 mm or more, more preferably 0.4 mm or more, and even more preferably 0.5 mm or more in order to obtain sufficient strength by the chemical strengthening treatment. The haze value of this tempered glass converted to a thickness of 0.7 mm is preferably 0.5% or less. The haze value and light transmittance of this chemically tempered glass are basically the same as those of crystallized glass before chemical tempering, so they will be explained in the section on crystallized glass.
[0035] The present tempered glass is preferably resistant to cracking due to deformation such as bending when the surface compressive stress value (CS0) is 400 MPa or more. CS0 is more preferably 500 MPa or more, and even more preferably 600 MPa or more. The higher the CS0, the higher the strength. However, if it is too high, there is a risk of severe shattering if cracked, so the surface compressive stress value (CS0) is preferably 1200 MPa or less, and more preferably 1000 MPa or less.
[0036] The DOL of the tempered glass is preferably 70 μm or more because the glass is less likely to break even if scratches are generated on the surface. The DOL is more preferably 80 μm or more, even more preferably 90 μm or more, and particularly preferably 100 μm or more. The larger the DOL, the less likely the glass is to break even if scratches are generated, but in chemically tempered glass, the DOL cannot be made extremely large because tensile stress is generated inside according to the compressive stress formed near the surface. The DOL is preferably t / 4 or less, and more preferably t / 5 or less, when the thickness is t. The DOL is preferably 200 μm or less, and more preferably 180 μm or less, in order to shorten the time required for chemical tempering.
[0037] The CT of the present tempered glass is preferably 110 MPa or less, since scattering of fragments is suppressed when the chemically tempered glass breaks. The CT is more preferably 100 MPa or less, and even more preferably 90 MPa or less. On the other hand, if the CT is reduced, the surface compressive stress tends to be reduced, making it difficult to obtain sufficient strength. Therefore, the CT is preferably 50 MPa or more, more preferably 55 MPa or more, and even more preferably 60 MPa or more.
[0038] In order to increase the drop resistance, the ST value of the tempered glass is preferably 18000MPa·μm or more, more preferably 20000MPa·μm or more, even more preferably 22000MPa·μm or more, and most preferably 24000MPa·μm or more. On the other hand, if the ST value is too high, glass fragments will scatter when crushed, so the ST value is preferably 30000MPa·μm or less, more preferably 29000MPa·μm or less, even more preferably 28000MPa·μm or less, and most preferably 27000MPa·μm or less.
[0039] The matrix composition of this tempered glass is expressed as mole percent based on oxides. SiO2 40-70%, Li2O 10~35%, It is preferable that the content of Al2O3 is 1 to 15%.
[0040] In addition, SiO2 is 40 to 70%, Li2O 10~35%, Al2O3 1-15%, P2O5 0.5-5%, ZrO2 0.5-5%, B2O3 0-10%, Na2O 0-3%, K2O 0-1%, Contains 0-4% SnO2. The total amount of SiO2, Al2O3, P2O5 and B2O3 is more preferably 60 to 80%.
[0041] Or, SiO2 50-70%, Li2O 15~30%, Al2O3 1-10%, P2O5 0.5-5%, ZrO2 0.5-8%, MgO 0.1-10%, Y2O3 0-5% B2O3 0-10%, Na2O 0-3%, K2O 0-1%, It is more preferable that SnO2 is contained in an amount of 0 to 2%.
[0042] Here, the "base composition of chemically strengthened glass" refers to the composition of crystallized glass before chemical strengthening. This composition will be described later. The composition of this strengthened glass is similar to that of crystallized glass before strengthening as a whole, except when extreme ion exchange treatment has been performed. In particular, the composition of the deepest part from the glass surface is the same as that of crystallized glass before strengthening, except when extreme ion exchange treatment has been performed.
[0043] The tempered glass is useful not only as a semiconductor support substrate described later, but also as a cover glass for electronic devices such as mobile devices such as mobile phones and smartphones. It is also useful as a cover glass for electronic devices such as televisions, personal computers, and touch panels that are not intended to be portable, elevator walls, and walls (full-surface displays) of buildings such as houses and buildings. It is also useful as building materials such as window glass, table tops, interiors of automobiles and airplanes, and cover glasses for these, and for curved housings. In addition, crystallized glass before tempering and amorphous glass before crystallization are also useful for semiconductor support substrates.
[0044] This semiconductor support substrate is a substrate used in the field of semiconductor packaging. In the field of semiconductor packaging, technologies such as wafer level packaging (WLP) and panel level packaging (PLP) are attracting attention in manufacturing (see Asahi Glass Research Report 67 (2017)). This technology involves, for example, placing a silicon chip on a glass substrate and sealing it by molding it with sealing resin.
[0045] In this case, the support substrate may be peeled off during the manufacturing process. Glass substrates are widely used as the support substrate. Since glass substrates are transparent, they can be peeled off by irradiating them with laser light. The glass substrate used as the support substrate is required to reduce warping by matching the thermal expansion with the semiconductor. Furthermore, it is required that the substrate is not easily broken during the packaging process, and that if it is broken, fragments do not scatter.
[0046] <Glass-ceramics> The present crystallized glass preferably contains at least one of Li3PO4 crystals and Li4SiO4 crystals. By using these crystals as the main crystals, the light transmittance is increased and the haze is reduced.
[0047] The present crystallized glass may contain both Li3PO4 crystals and Li4SiO4 crystals. It may contain either one of them as the main crystal. It may be a solid solution crystal of Li3PO4 and Li4SiO4 as the main crystal. It may also be a solid solution crystal of either Li3PO4 or Li4SiO4 as the main crystal.
[0048] However, since Li2SiO3 crystal does not have good chemical resistance, it is preferable not to include it.
[0049] Li3PO4 crystals and Li4SiO4 crystals have similar crystal structures, so it can be difficult to distinguish them by powder X-ray diffraction measurements. In other words, when measuring powder X-ray diffraction for both, diffraction peaks appear around 2θ = 16.9°, 22.3°, 23.1°, and 33.9°. In some cases, the amount of crystals is small or they are oriented, so low-intensity peaks or peaks on specific crystal planes may not be visible. In addition, when both crystals are in solid solution, the peak position may shift by about 1° at 2θ.
[0050] When the present glass-ceramics is measured by X-ray diffraction in the range of 2θ=10 to 80°, the strongest diffraction peak preferably appears at 22.3°±0.2° or 23.1°±0.2°.
[0051] The crystallization rate of the present crystallized glass is preferably 5% or more, more preferably 10% or more, even more preferably 15% or more, and particularly preferably 20% or more in order to increase mechanical strength. In order to increase transparency, it is preferably 70% or less, more preferably 60% or less, and even more preferably 50% or less. A small crystallization rate is also excellent in that it is easy to bend and mold by heating.
[0052] The average particle size of the precipitated crystals of the present crystallized glass is preferably 5 nm or more, particularly preferably 10 nm or more, in order to increase strength. In order to increase transparency, it is preferably 80 nm or less, more preferably 60 nm or less, even more preferably 50 nm or less, particularly preferably 40 nm or less, and most preferably 30 nm or less. The average particle size of the precipitated crystals is obtained from a transmission electron microscope (TEM) image or a FE-SEM image.
[0053] When the crystallized glass is in the form of a plate, the thickness (t) is preferably 3 mm or less, more preferably 2 mm or less, 1.6 mm or less, 1.1 mm or less, 0.9 mm or less, 0.8 mm or less, and 0.7 mm or less in the following stepwise manner. In addition, the thickness (t) is preferably 0.3 mm or more, more preferably 0.4 mm or more, and even more preferably 0.5 mm or more, in order to obtain sufficient strength by chemical strengthening treatment.
[0054] The light transmittance of this crystallized glass is 85% or more when the thickness is 0.7 mm, so when used as a cover glass for a mobile display, the display screen is easy to see. The light transmittance is preferably 88% or more, and more preferably 90% or more. The higher the light transmittance, the better, but it is usually 91% or less. When the thickness is 0.7 mm, the light transmittance of 90% is equivalent to that of ordinary amorphous glass.
[0055] If the actual thickness is not 0.7 mm, the light transmittance for a thickness of 0.7 mm can be calculated from the measured value using the Lambert-Beer law. If the plate thickness t is greater than 0.7 mm, the plate thickness may be adjusted to 0.7 mm by polishing or etching before measurement.
[0056] In addition, the haze value is 0.5% or less when the thickness is 0.7 mm, preferably 0.3% or less, more preferably 0.2% or less, even more preferably 0.15% or less, particularly preferably 0.1% or less, most preferably 0.08%, and extremely preferably 0.05% or less. The smaller the haze value, the better, but it is usually 0.01% or more. When the thickness is 0.7 mm, the haze value of 0.02% is equivalent to that of ordinary amorphous glass.
[0057] If the total light visible transmittance of crystallized glass with a thickness of t [mm] is 100×T [%] and the haze value is 100×H [%], then by applying the Beer-Lambert law, it can be written as T = (1-R)2 × exp(-αt) using the constant α. Using this constant α, dH / dt ∝ exp(-αt) × (1-H). In other words, the haze value can be considered to increase in proportion to the internal linear transmittance as the plate thickness increases. 0.7 is calculated using the following formula:
[0058]
number
[0059] Moreover, if the plate thickness t is greater than 0.7 mm, the plate thickness may be adjusted to 0.7 mm by polishing, etching, or the like before measurement.
[0060] The ST limit of this crystallized glass is preferably 18000MPa·μm or more. The ST limit is more preferably 19000MPa·μm or more, and even more preferably 20000MPa·μm or more, because the drop resistance can be increased by chemical strengthening. Since this crystallized glass has a large ST limit, it is difficult to break even if it is made high strength by chemical strengthening. The higher the ST limit, the better, but it is usually 30000MPa·μm or less.
[0061] The present crystallized glass can be obtained by heat treating and crystallizing an amorphous glass, which will be described later.
[0062] This crystallized glass is expressed as mole percent based on oxides, SiO2 40-70%, Li2O 10~35%, Al2O3 1-15%, P2O5 0.5-5%, ZrO2 0.5-5%, B2O3 0-10%, Na2O 0-3%, K2O 0-1%, It is preferable that the glass contains 0 to 4% of SnO2. In this specification, the crystallized glass having this composition is also referred to as "the present crystallized glass A".
[0063] Or, in mole percent based on oxide, SiO2 50-70%, Li2O 15~30%, Al2O3 1-10%, P2O5 0.5-5%, ZrO2 0.5-8%, MgO 0.1-10%, Y2O3 0-5% B2O3 0-10%, Na2O 0-3%, K2O 0-1%, It is preferable that the glass contains 0 to 2% of SnO2. In this specification, the crystallized glass having such a composition is also referred to as "the present crystallized glass B".
[0064] In addition, the present crystallized glass preferably has a total content of SiO2, Al2O3, P2O5 and B2O3 of 60 to 80% in terms of mole percent based on oxides. SiO2, Al2O3, P2O5 and B2O3 are glass network forming components (hereinafter also abbreviated as NWF). The greater the total content of these NWFs, the stronger the glass. This increases the fracture toughness value of the crystallized glass, so the total content of NWFs is preferably 60% or more, more preferably 63% or more, and particularly preferably 65% or more. However, glass with too much NWF has a high melting temperature and is difficult to manufacture, so the total content is preferably 80% or less, more preferably 75%, and more preferably 70% or less.
[0065] In the crystallized glass, the ratio of the total amount of Li2O, Na2O and K2O to the total amount of NWF, i.e., SiO2, Al2O3, P2O5 and B2O3, is preferably 0.20 to 0.60. For semiconductor support substrates, if the ratio of the content of Al2O3 to Li2O, Al2O3 / Li2O, is 0.0029 to 0.0075 to the total amount of NWF, Young's modulus can be increased while maintaining a thermal expansion coefficient suitable for a support substrate for semiconductor packages with a large resin content, and warpage during the packaging process can be reduced. The lower limit is preferably 0.0031 or more, more preferably 0.0032 or more, and the upper limit is preferably 0.0064 or less, more preferably 0.0051 or less. As a component for increasing Young's modulus, Al2O3 is the most effective, but other examples include MgO, ZrO2, Y2O3, Ga2O3, BeO, TiO2, and Ta2O5.
[0066] Li2O, Na2O and K2O are network modifiers, and reducing the ratio to NWF increases the gaps in the network, improving impact resistance. Therefore, the ratio of the total amount of Li2O, Na2O and K2O to the total amount of NWF, i.e., SiO2, Al2O3, P2O5 and B2O3, is preferably 0.60 or less, more preferably 0.55 or less, and particularly preferably 0.50 or less. On the other hand, since these are necessary components for chemical strengthening, in order to improve the chemical strengthening properties, the ratio of the total amount of Li2O, Na2O and K2O to the total amount of NWF, i.e., SiO2, Al2O3, P2O5 and B2O3, is preferably 0.20 or more, more preferably 0.25 or more, and particularly preferably 0.30 or more. The glass composition will be described below.
[0067] In the present amorphous glass, SiO2 is a component that forms a network structure of glass. It is also a component that increases chemical durability, and the SiO2 content is preferably 40% or more. The SiO2 content is more preferably 45% or more, even more preferably 50% or more, particularly preferably 52% or more, and extremely preferably 54% or more. On the other hand, in order to improve melting property, the SiO2 content is preferably 70% or less, more preferably 68% or less, even more preferably 66% or less, and particularly preferably 64% or less.
[0068] Al2O3 is a component that increases the surface compressive stress due to chemical strengthening, and is essential. The content of Al2O3 is preferably 1% or more, more preferably 2% or more, further preferably 3% or more, 5% or more, 5.5% or more, 6% or more, particularly preferably 6.5% or more, and most preferably 7% or more. On the other hand, the content of Al2O3 is preferably 15% or less, more preferably 12% or less, further preferably 10% or less, particularly preferably 9% or less, and most preferably 8% or less, so that the devitrification temperature of the glass does not become too high.
[0069] Li2O is a component that forms surface compressive stress by ion exchange, and is essential because it is a component of the main crystal. The content of Li2O is preferably 10% or more, more preferably 14% or more, more preferably 15% or more, even more preferably 18% or more, particularly preferably 20% or more, and most preferably 22% or more. On the other hand, in order to stabilize the glass, the content of Li2O is preferably 35% or less, more preferably 32% or less, even more preferably 30% or less, particularly preferably 28% or less, and most preferably 26% or less.
[0070] Na2O is a component that improves the melting property of glass. Na2O is not essential, but when it is contained, it is preferably 0.5% or more, more preferably 1% or more, and particularly preferably 2% or more. If there is too much Na2O, crystals are difficult to precipitate or the chemical strengthening properties are reduced, so the content of Na2O is preferably 3% or less, more preferably 2.5% or less, even more preferably 2% or less, and particularly preferably 1.5% or less.
[0071] K2O is a component that lowers the melting temperature of glass like Na2O, and may be contained. When K2O is contained, the content is preferably 0.5% or more, more preferably 0.8% or more, and even more preferably 1% or more. If the amount of K2O is too much, the chemical strengthening properties or chemical durability will decrease, so the content is preferably 1% or less, more preferably 0.8% or less, even more preferably 0.6% or less, particularly preferably 0.5% or less, and most preferably 0.4% or less.
[0072] The total content of Na2O and K2O, Na2O+K2O, is preferably 1% or more, and more preferably 2% or more, in order to improve the meltability of the glass raw materials.
[0073] In addition, the ratio of the K2O content to the total content of Li2O, Na2O and K2O (hereinafter referred to as R2O) is preferably 0.2 or less, since this improves the chemical strengthening properties and chemical durability. K2O / R2O is more preferably 0.15 or less, and even more preferably 0.10 or less.
[0074] R2O is preferably 10% or more, more preferably 15% or more, and even more preferably 20% or more. R2O is preferably 29% or less, and more preferably 26% or less.
[0075] P2O5 is a component of Li3PO4 crystal and is essential. The content of P2O5 is preferably 0.5% or more, more preferably 1% or more, even more preferably 1.5% or more, particularly preferably 2% or more, and extremely preferably 2.5% or more in order to promote crystallization. On the other hand, if the content of P2O5 is too high, phase separation occurs easily during melting and acid resistance is significantly reduced, so the content of P2O5 is preferably 5% or less, more preferably 4.8% or less, even more preferably 4.5% or less, and particularly preferably 4.2% or less.
[0076] ZrO2 is a component that enhances mechanical strength and chemical durability, and is preferably contained because it significantly improves CS. The content of ZrO2 is preferably 0.5% or more, more preferably 1% or more, even more preferably 1.5% or more, particularly preferably 2% or more, and most preferably 2.5% or more. On the other hand, in order to suppress devitrification during melting, ZrO2 is preferably 8% or less, more preferably 7.5% or less, even more preferably 7% or less, and particularly preferably 6% or less. If the content of ZrO2 is too high, the viscosity decreases due to an increase in the devitrification temperature. In order to suppress deterioration of moldability due to such a decrease in viscosity, when the molding viscosity is low, the content of ZrO2 is preferably 5% or less, more preferably 4.5% or less, and even more preferably 3.5% or less.
[0077] In order to improve chemical durability, ZrO2 / R2O is preferably 0.02 or more, more preferably 0.03 or more, even more preferably 0.04 or more, particularly preferably 0.1 or more, and most preferably 0.15 or more. In order to improve transparency after crystallization, ZrO2 / R2O is preferably 0.6 or less, more preferably 0.5 or less, even more preferably 0.4 or less, and particularly preferably 0.3 or less.
[0078] Since MgO is a component that stabilizes glass and also enhances mechanical strength and chemical resistance, it is preferable to contain it when the Al2O3 content is relatively low. The content of MgO is preferably 1% or more, more preferably 2% or more, even more preferably 3% or more, and particularly preferably 4% or more. On the other hand, if too much MgO is added, the viscosity of the glass decreases and devitrification or phase separation is likely to occur, so the content of MgO is preferably 10% or less, more preferably 9% or less, even more preferably 8% or less, and particularly preferably 7% or less.
[0079] TiO2 is a component that can promote crystallization and may be contained. TiO2 is not essential, but if it is contained, it is preferably 0.2% or more, more preferably 0.5% or more. On the other hand, in order to suppress devitrification during melting, the content of TiO2 is preferably 4% or less, more preferably 2% or less, and even more preferably 1% or less.
[0080] SnO2 has the effect of promoting the formation of crystal nuclei and may be contained. SnO2 is not essential, but when it is contained, it is preferably 0.5% or more, more preferably 1% or more, even more preferably 1.5% or more, and particularly preferably 2% or more. On the other hand, in order to suppress devitrification during melting, the content of SnO2 is preferably 4% or less, more preferably 3.5% or less, even more preferably 3% or less, and particularly preferably 2.5% or less.
[0081] Y2O3 is a component that has the effect of preventing fragments from scattering when the chemically strengthened glass is broken, and may be contained. The content of Y2O3 is preferably 1% or more, more preferably 1.5% or more, even more preferably 2% or more, particularly preferably 2.5% or more, and extremely preferably 3% or more. On the other hand, in order to suppress devitrification during melting, the content of Y2O3 is preferably 5% or less, more preferably 4% or less.
[0082] B2O3 is a component that improves the chipping resistance of the chemically strengthened glass or the chemically strengthened glass and improves the meltability, and may be contained. When B2O3 is contained, the content is preferably 0.5% or more, more preferably 1% or more, and even more preferably 2% or more in order to improve the meltability. On the other hand, if the content of B2O3 is too high, striae may occur during melting, or phase separation may occur easily, which may lead to a deterioration in the quality of the chemically strengthened glass, so that the content is preferably 10% or less. The content of B2O3 is more preferably 8% or less, even more preferably 6% or less, and particularly preferably 4% or less.
[0083] BaO, SrO, MgO, CaO and ZnO are all components that improve the melting property of glass and may be contained. When these components are contained, the total content of BaO, SrO, MgO, CaO and ZnO (hereinafter, BaO+SrO+MgO+CaO+ZnO) is preferably 0.5% or more, more preferably 1% or more, even more preferably 1.5% or more, and particularly preferably 2% or more. On the other hand, since the ion exchange rate decreases, BaO+SrO+MgO+CaO+ZnO is preferably 8% or less, more preferably 6% or less, even more preferably 5% or less, and particularly preferably 4% or less.
[0084] Among these, BaO, SrO, and ZnO may be contained to improve the refractive index of the residual glass and bring it closer to the precipitated crystal phase, thereby improving the light transmittance of the crystallized glass and reducing the haze value. In this case, the total content of BaO, SrO, and ZnO (hereinafter, BaO+SrO+ZnO) is preferably 0.3% or more, more preferably 0.5% or more, even more preferably 0.7% or more, and particularly preferably 1% or more. On the other hand, these components may reduce the ion exchange rate. In order to improve the chemical strengthening properties, BaO+SrO+ZnO is preferably 2.5% or less, more preferably 2% or less, even more preferably 1.7% or less, and particularly preferably 1.5% or less.
[0085] La2O3, Nb2O5 and Ta2O5 are all components that make it difficult for chemically strengthened glass to scatter fragments when broken, and may be contained to increase the refractive index. When these are contained, the total content of La2O3, Nb2O5 and Ta2O5 (hereinafter, La2O3+Nb2O5+Ta2O5) is preferably 0.5% or more, more preferably 1% or more, even more preferably 1.5% or more, and particularly preferably 2% or more. In addition, in order to make the glass less susceptible to devitrification during melting, La2O3+Nb2O5+Ta2O5 is preferably 4% or less, more preferably 3% or less, even more preferably 2% or less, and particularly preferably 1% or less.
[0086] CeO2 may also be contained. CeO2 may suppress coloring by oxidizing the glass. When CeO2 is contained, the content is preferably 0.03% or more, more preferably 0.05% or more, and even more preferably 0.07% or more. In order to increase transparency, the content of CeO2 is preferably 1.5% or less, and more preferably 1.0% or less.
[0087] When the tempered glass is colored, a coloring component may be added to the glass within a range that does not impede the achievement of the desired chemical strengthening properties. Examples of the coloring component include Co3O4, MnO2, Fe2O3, NiO, CuO, Cr2O3, V2O5, Bi2O3, SeO2, Er2O3, and Nd2O3.
[0088] The total content of coloring components is preferably within the range of 1% or less. If it is desired to increase the visible light transmittance of the glass, it is preferable that these components are substantially not contained.
[0089] In order to improve weather resistance against ultraviolet light irradiation, HfO2, Nb2O5, and Ti2O3 may be added. When added for the purpose of improving weather resistance against ultraviolet light irradiation, the total content of HfO2, Nb2O5, and Ti2O3 is preferably 1% or less, more preferably 0.5% or less, and even more preferably 0.1% or less, in order to suppress the influence on other properties.
[0090] In addition, SO3, chlorides, and fluorides may be appropriately contained as clarifiers for melting glass. The total content of components functioning as clarifiers is preferably 2% or less, more preferably 1% or less, and even more preferably 0.5% or less, expressed as mass% on an oxide basis, since adding too much of them affects the strengthening characteristics and crystallization behavior. The lower limit is not particularly limited, but typically, the total content is preferably 0.05% or more, expressed as mass% on an oxide basis.
[0091] When SO3 is used as a fining agent, the content of SO3 is preferably 0.01% or more, more preferably 0.05% or more, and even more preferably 0.1% or more, expressed as mass% on the oxide basis, since the effect is not observed if the content is too small. Also, when SO3 is used as a fining agent, the content of SO3 is preferably 1% or less, more preferably 0.8% or less, and even more preferably 0.6% or less, expressed as mass% on the oxide basis.
[0092] When Cl is used as a fining agent, if too much is added, it affects physical properties such as strengthening characteristics, so the Cl content is preferably 1% or less, more preferably 0.8% or less, and even more preferably 0.6% or less, expressed as mass % on the oxide basis. Also, if Cl is used as a fining agent, if the Cl content is too low, no effect is observed, so the Cl content is preferably 0.05% or more, more preferably 0.1% or more, and even more preferably 0.2% or more, expressed as mass % on the oxide basis.
[0093] When SnO2 is used as a clarifier, the content of SnO2 is preferably 1% or less, more preferably 0.5% or less, and even more preferably 0.3% or less, expressed as mass% on the oxide basis, since too little SnO2 content affects crystallization behavior. Also, when SnO2 is used as a clarifier, the content of SnO2 is not effective if it is too little, so it is preferably 0.02% or more, more preferably 0.05% or more, and even more preferably 0.1% or more, expressed as mass% on the oxide basis.
[0094] It is preferable that As2O3 is not contained. When Sb2O3 is contained, the content is preferably 0.3% or less, more preferably 0.1% or less, and most preferably, no Sb2O3 is contained.
[0095] This glass-ceramic has a high fracture toughness value, and is unlikely to break violently even when a large compressive stress is applied by chemical strengthening. The fracture toughness value of this glass-ceramic is preferably 0.81 MPa m 1 / 2 More preferably, 0.83 MPa m 1 / 2 More preferably, 0.85 MPa m 1 / 2If the fracture toughness is above this value, a glass with high impact resistance can be obtained. There is no particular upper limit for the fracture toughness of the present glass-ceramics, but it is typically 1.5 MPa m 1 / 2 The following is the result.
[0096] The Young's modulus of the present crystallized glass is preferably 80 GPa or more, more preferably 85 GPa or more, even more preferably 90 GPa or more, and particularly preferably 95 GPa or more, in order to suppress warpage during chemical strengthening treatment. The present crystallized glass may be polished before use. In order to facilitate polishing, the Young's modulus is preferably 130 GPa or less, more preferably 120 GPa or less, and even more preferably 110 GPa or less.
[0097] In addition, if the Young's modulus of amorphous glass is 80GPa or more, it can suppress warpage even in the amorphous glass state, so it is suitable for use as a semiconductor support substrate.Preferably, it is 85GPa or more, more preferably 90GPa or more, and even more preferably 95GPa or more.For ease of polishing, the Young's modulus is preferably 130GPa or less, more preferably 120GPa or less, and even more preferably 110GPa or less.
[0098] The indentation load (CIL) at which the number of cracks in the present crystallized glass becomes two is preferably 50 gf or more, more preferably 100 gf or more, even more preferably 150 gf or more, and most preferably 200 gf or more, from the viewpoint of suppressing the occurrence of cracks when dropped.
[0099] <Amorphous glass> The present crystallized glass can be obtained by heat-treating the amorphous glass described below (the amorphous glass according to the present invention). The composition of the amorphous glass according to the present invention is the same as that of the present crystallized glass described above.
[0100] The amorphous glass according to the present invention (hereinafter also referred to as the present amorphous glass) preferably contains, in mole % on an oxide basis, 40 to 70% SiO2, 10 to 35% Li2O, and 1 to 15% Al2O3.
[0101] A preferred composition of the present amorphous glass is, for example, a composition containing, in mole % on an oxide basis, 40-70% SiO2, 10-35% Li2O, 1-15% Al2O3, 0.5-5% P2O5, 0.5-5% ZrO2, 0-10% B2O3, 0-3% Na2O, 0-1% K2O, and 0-4% SnO2.
[0102] Alternatively, a preferred composition of the present amorphous glass may include, for example, a composition containing, in mole % on an oxide basis, 50-70% SiO2, 15-30% Li2O, 1-10% Al2O3, 0.5-5% P2O5, 0.5-8% ZrO2, 0.1-10% MgO, 0-5% Y2O3, 0-10% B2O3, 0-3% Na2O, 0-1% K2O, and 0-2% SnO2.
[0103] In the present amorphous glass, the total amount of SiO2, Al2O3, P2O5 and B2O3 is preferably 60 to 80%. Also, the ratio of the total amount of Li2O, Na2O and K2O to the total amount of SiO2, Al2O3, P2O5 and B2O3 is preferably 0.20 to 0.60.
[0104] The glass transition temperature Tg of the present amorphous glass is preferably 400° C. or higher, more preferably 450° C. or higher, and even more preferably 500° C. or higher, in order to prevent structural relaxation during chemical strengthening. Also, it is preferably 650° C. or lower, and more preferably 600° C. or lower.
[0105] The amorphous glass is crushed, and the difference (Tx-Tg) between the glass transition point (Tg) determined from a DSC curve obtained using a differential scanning calorimeter and the crystallization onset temperature (Tx) appearing in the lowest temperature range in the DSC curve is preferably 50° C. or higher, more preferably 60° C. or higher, even more preferably 70° C. or higher, and particularly preferably 80° C. or higher. If (Tx-Tg) is large, the crystallized glass can be easily reheated and bent.
[0106] The average thermal expansion coefficient of this amorphous glass at 50℃ to 350℃ is 70×10 -7 ℃ or higher is preferable, 75×10-7 °C or higher is preferable, and 80 × 10 -7 °C or higher is most preferred.
[0107] If the thermal expansion coefficient is too large, cracks may occur due to the difference in thermal expansion during the chemical strengthening process. Therefore, it is preferable to set the thermal expansion coefficient at 120×10 -7 °C or less, more preferably 110 × 10 -7 °C or less, more preferably 100 × 10 -7 °C or less.
[0108] Furthermore, such a thermal expansion coefficient makes the material suitable for use as a support substrate for semiconductor packages that contain a large amount of resin.
[0109] <Method of manufacturing chemically strengthened glass> The chemically strengthened glass of the present invention is produced by subjecting crystallized glass to a chemical strengthening treatment. The crystallized glass is produced by a method of heat-treating the aforementioned amorphous glass to crystallization.
[0110] (Production of amorphous glass) The amorphous glass can be produced, for example, by the following method. Note that the production method described below is an example of the case of producing a plate-shaped chemically strengthened glass.
[0111] Glass raw materials are mixed so as to obtain glass of a desired composition, and are heated and melted in a glass melting furnace. The molten glass is then homogenized by bubbling, stirring, adding a clarifier, etc., and formed into a glass plate of a predetermined thickness by a known forming method, and slowly cooled. Alternatively, the molten glass may be formed into a block shape, slowly cooled, and then cut into a plate shape.
[0112] (Crystallization treatment) The amorphous glass obtained by the above procedure is subjected to a heat treatment (for example, preferably at 450° C. or higher and 800° C. or lower) to obtain crystallized glass.
[0113] The heat treatment may be a two-stage heat treatment in which the temperature is raised from room temperature to a first treatment temperature and held for a certain period of time, and then held for a certain period of time at a second treatment temperature higher than the first treatment temperature, or a one-stage heat treatment in which the temperature is held at a specific treatment temperature and then cooled to room temperature.
[0114] In the case of two-stage heat treatment, the first treatment temperature is preferably in a temperature range where the crystal nucleation rate is high in the glass composition, and the second treatment temperature is preferably in a temperature range where the crystal growth rate is high in the glass composition. Also, the holding time at the first treatment temperature is preferably long so that a sufficient number of crystal nuclei are generated. By generating a large number of crystal nuclei, the size of each crystal becomes small, and a highly transparent crystallized glass is obtained.
[0115] In the case of a two-stage treatment, for example, a first treatment temperature of 450° C. to 700° C. is held for 1 to 6 hours, and then a second treatment temperature of 600° C. to 800° C. is held for 1 to 6 hours. In the case of a one-stage treatment, for example, a temperature of 500° C. to 800° C. is held for 1 to 6 hours.
[0116] The molten glass may be homogenized and formed into a glass plate of a predetermined thickness, or may be formed into a block shape, followed by continuous crystallization treatment.
[0117] When plate-shaped glass is heat-treated, examples of the setter plate include a silicon carbide plate, a silicon nitride plate, a SiN plate, an alumina plate, a mullite-cordierite plate, a mullite plate, and a crystallized glass plate. In addition, a material with a high thermal conductivity is preferable to reduce temperature unevenness during heat treatment. The thermal conductivity of the setter plate is preferably 2 W / (m·K) or more, more preferably 20 W / (m·K) or more, and even more preferably 40 W / (m·K) or more.
[0118] A release agent can be used to prevent the glass from adhering to the setter plate. Examples of the release agent include alumina cloth and glass cloth. Other examples include powdered boron nitride, alumina, and minerals. A powdered release agent may be mixed with a solvent and applied by spraying or the like. When a particulate one is used, the average particle size is preferably 80 μm or less, more preferably 50 μm or less, and even more preferably 30 μm or less.
[0119] When the glass is heat-treated, it may be laminated to improve the working efficiency. When laminating, it is preferable to use a release agent between the glass sheets. Also, a setter plate may be placed between the glass sheets.
[0120] The crystallized glass obtained by the above procedure is ground and polished as necessary to form a crystallized glass plate. When the crystallized glass plate is cut into a predetermined shape and size or chamfered, it is preferable to perform the cutting or chamfering before the chemical strengthening treatment, because a compressive stress layer is formed on the end surface by the subsequent chemical strengthening treatment.
[0121] (Chemical strengthening treatment) Chemical strengthening is a process in which glass is brought into contact with a metal salt, for example by immersing the glass in a molten liquid of a metal salt (e.g., potassium nitrate) containing a metal ion with a large ionic radius (typically, Na ion or K ion), thereby replacing the metal ion with a small ionic radius (typically, Na ion or Li ion) in the glass with a metal ion with a large ionic radius (typically, Na ion or K ion for Li ion, and K ion for Na ion).
[0122] In order to increase the speed of chemical strengthening, it is preferable to use "Li-Na exchange" in which Li ions in the glass are exchanged with Na ions. Also, in order to create a large compressive stress by ion exchange, it is preferable to use "Na-K exchange" in which Na ions in the glass are exchanged with K ions.
[0123] Examples of molten salts for performing chemical strengthening treatment include nitrates, sulfates, carbonates, and chlorides. Examples of nitrates include lithium nitrate, sodium nitrate, potassium nitrate, cesium nitrate, and silver nitrate. Examples of sulfates include lithium sulfate, sodium sulfate, potassium sulfate, cesium sulfate, and silver sulfate. Examples of carbonates include lithium carbonate, sodium carbonate, and potassium carbonate. Examples of chlorides include lithium chloride, sodium chloride, potassium chloride, cesium chloride, and silver chloride. These molten salts may be used alone or in combination.
[0124] The conditions of the chemical strengthening treatment can be selected, such as time and temperature, taking into consideration the glass composition and the type of molten salt. For example, the present crystallized glass can be chemically strengthened at 450° C. or less for preferably 1 hour or less. Specifically, for example, the present glass can be immersed in a molten salt (e.g., a mixed salt of lithium nitrate and sodium nitrate) containing 0.3 mass % Li and 99.7 mass % Na at 450° C. for preferably about 0.5 hours.
[0125] The chemical strengthening treatment may be, for example, a two-stage ion exchange treatment as follows: First, the present crystallized glass is immersed in a metal salt (e.g., sodium nitrate) containing Na ions at about 350 to 500° C. for about 0.1 to 10 hours. This causes ion exchange between the Li ions in the crystallized glass and the Na ions in the metal salt, forming a relatively deep compressive stress layer.
[0126] Next, the sample is immersed in a metal salt (e.g., potassium nitrate) containing K ions at a temperature of preferably about 350 to 500° C. for about 0.1 to 10 hours. This generates a large compressive stress in the compressive stress layer formed in the previous treatment, for example, within a depth of about 10 μm. Such a two-stage treatment makes it easy to obtain a stress profile with a large surface compressive stress value.
[0127] <Semiconductor support substrate> The semiconductor support substrate of the present invention (hereinafter, also referred to as support glass) will be described. The semiconductor support substrate of the present invention is made of the amorphous glass or crystallized glass of the present invention. In order to increase the strength, it is more preferable that the semiconductor support substrate is made of the tempered glass of the present invention.
[0128] The present amorphous glass, crystallized glass, or tempered glass has a large thermal expansion coefficient, and is therefore suitable as a support substrate for fan-out type packages. In fan-out type packaging, packages with various average thermal expansion coefficients are formed depending on the ratio of semiconductor chips to resin components, but in recent years, packages with a large amount of resin components and a high average thermal expansion coefficient are often used because there is a demand for high fluidity of mold resin and reduced filling defects.
[0129] 6(A) and 6(B) are examples of cross-sectional views of a supporting glass to be bonded to a semiconductor substrate. The supporting glass G1 shown in FIG. 6(A) is bonded to a semiconductor substrate 10 via a peeling layer 20 (which may function as a bonding layer) at a temperature of, for example, 200°C to 400°C to obtain a laminated substrate 30 shown in FIG. 6(B). As the semiconductor substrate 10, for example, a full-sized semiconductor wafer, a semiconductor chip, a substrate in which a semiconductor chip is molded in a resin, a wafer on which elements are formed, or the like is used. The peeling layer 20 is, for example, a resin that can withstand temperatures of 200°C to 400°C.
[0130] This support substrate is used by being bonded to a semiconductor substrate. For example, it is used as support glass for fan-out type wafer level packages, support glass for image sensors such as MEMS, CMOS and CIS, in which miniaturization of elements by wafer level packages is effective, support glass with through holes (glass interposer; GIP), and support glass for semiconductor back grinding. This support glass is particularly suitable as support glass for fan-out type wafer level and panel level packages.
[0131] FIG. 7 is an example of a cross-sectional view of a laminated substrate in which the supporting glass is used as a supporting substrate for a fan-out type wafer-level package.
[0132] In the fan-out type wafer level package, for example, at a temperature of 200°C to 400°C, the support glass G2 and the semiconductor substrate 40 are laminated via a release layer 50 (which may function as a bonding layer) such as resin. The semiconductor substrate 40 is further embedded in the resin 60 to obtain the laminated substrate 70. Thereafter, the support glass G2 and the semiconductor substrate 40 embedded in the resin 60 are peeled off by irradiating the release layer 50 with, for example, ultraviolet light or a laser through the support glass G2. The support glass G2 is reusable. The single conductor substrate 40 embedded in the resin 60 is wired with copper wires or the like. Also, wiring with copper wires or the like may be performed in advance on the release layer. The substrate in which the semiconductor chip is embedded in the resin 60 may be used as the semiconductor substrate.
[0133] Since the supporting substrate has high light transmittance, a visible light laser or an ultraviolet light laser having high energy can be effectively used as the laser for peeling. EXAMPLES
[0134] The present invention will be described below with reference to examples, but the present invention is not limited thereto.
[0135] [Experimental Example 1] <Preparation and evaluation of amorphous glass> The glass raw materials were mixed to obtain the glass compositions shown in Tables 1 and 2 in terms of oxide-based mole percent, and weighed out to obtain 800 g of glass. The mixed glass raw materials were then placed in a platinum crucible and placed in an electric furnace at 1600°C to melt for about 5 hours, degassed, and homogenized.
[0136] The obtained molten glass was poured into a mold and held at the glass transition temperature for 1 hour, and then cooled to room temperature at a rate of 0.5°C / min to obtain a glass block. Using a portion of the obtained block, the glass transition temperature, specific gravity, Young's modulus, fracture toughness value, and thermal expansion coefficient of the amorphous glass were evaluated, and the results are shown in Tables 1 and 2.
[0137] Blanks in the table indicate that no evaluation has been performed. In the table, R2O represents the total content of Li2O, Na2O, and K2O, and NWF represents the total content of SiO2, Al2O3, P2O5, and B2O3.
[0138] G3 to G8, G11, G13, and G14 are examples of amorphous glasses according to the present invention, and G1, G2, G9, G10, G12, G15, and G16 are comparative examples.
[0139] (specific gravity ρ) Measured by Archimedes method.
[0140] (glass transition temperature Tg) The glass was crushed using an agate mortar, and about 80 mg of the powder was placed in a platinum cell. The temperature was raised from room temperature to 1100°C at a heating rate of 10 min-1. The DSC curve was measured using a differential scanning calorimeter (DSC3300SA, manufactured by Bruker) to determine the glass transition point Tg. Alternatively, based on JIS R1618:2002, a thermal expansion curve was obtained using a thermal dilatometer (TD5000SA manufactured by Bruker AXS) at a heating rate of 10°C / min, and the glass transition point Tg [unit: °C] and the thermal expansion coefficient [unit: 1 / K] were calculated from the obtained thermal expansion curve.
[0141] (Haze value) The haze value (unit: %) was measured using a haze meter (HZ-V3 manufactured by Suga Test Instruments) with a halogen lamp C light source.
[0142] (Young's modulus E) Measurements were taken using the ultrasonic pulse method (JIS R1602).
[0143] (Fracture toughness value Kc) Measurements were performed using the IF method in accordance with JIS R1607:2015.
[0144] [Table 1]
[0145] [Table 2]
[0146] <Crystallization treatment and evaluation of crystallized glass> The obtained glass block was processed to 50 mm × 50 mm × 1.5 mm, and then heat-treated under the conditions shown in Tables 3 and 4 to obtain crystallized glass. In the crystallization condition column in the table, the upper row shows the nucleation treatment conditions, and the lower row shows the crystal growth treatment conditions. For example, if the upper row shows 550°C for 2 hours and the lower row shows 730°C for 2 hours, it means that the material was held at 550°C for 2 hours, and then held at 730°C for 2 hours.
[0147] The effect of release agents in crystallization treatment was confirmed. When G13 glass was heat treated on an alumina setter plate without using a release agent, the glass adhered to the setter plate. When boron nitride was used as the release agent, there was no adhesion between the glass and the setter plate, and crystallized glass was obtained. When alumina cloth, alumina sheet, alumina particles, glass cloth, or talc were used as the release agent, there was no adhesion between the glass and the setter plate, and crystallized glass was obtained.
[0148] Glass G13 was heat-treated using an alumina sheet as a release agent and a SiC plate, an alumina plate, a mullite-cordierite plate, and a mullite plate as a setter plate. As a result, crystallized glass was obtained in all cases.
[0149] Examples 4, 5, 7, 9, and 12 to 14 are working examples, and Examples 1 to 3, 6, 8, 10, and 11 are comparative examples.
[0150] The obtained crystallized glass was processed and mirror-polished to obtain a crystallized glass plate with a thickness t of 0.7 mm. A rod-shaped sample was also prepared to measure the thermal expansion coefficient. A portion of the remaining crystallized glass was crushed and used to analyze the precipitated crystals. The evaluation results of the crystallized glass are shown in Tables 3 to 4. Blanks indicate that no evaluation was performed.
[0151] (X-ray diffraction: precipitated crystals) Powder X-ray diffraction was measured under the following conditions to identify the precipitated crystals. Measurement equipment: Rigaku Smart Lab X-ray used: CuKα ray Measurement range: 2θ=10°~80° Speed: 1° / min Step: 0.01°
[0152] The main crystals detected are shown in the crystal columns of Tables 3 and 4. Because it is difficult to distinguish between Li3PO4 and Li4SiO4 by powder X-ray diffraction, both are listed. Figure 1 shows the results of X-ray diffraction measurement of the crystallized glass of Example 4.
[0153] (Haze value) The haze value (unit: %) was measured using a haze meter (HZ-V3 manufactured by Suga Test Instruments) with a halogen lamp C light source.
[0154] (CIL) A plate-shaped glass with a thickness of 0.7 mm, mirror-polished on both sides, was prepared. A Vickers indenter (tip angle 136°) was pressed into the glass using a Vickers hardness tester for 15 seconds, and then the Vickers indenter was removed, and the area around the indentation was observed after 15 seconds. In the observation, the number of cracks generated from the corners of the indentation was investigated. Measurements were performed on 10 pieces of glass at Vickers indenter indentation loads of 10gf, 25gf, 50gf, 100gf, 200gf, 300gf, and 500gf. The average number of cracks generated was calculated for each load. The relationship between the load and the number of cracks was calculated by regression calculation using a sigmoid function. From the regression calculation results, the load at which the number of cracks became two was determined as the indentation load value (gf). The atmospheric conditions for the measurement were an air temperature of 25°C and a dew point of -40°C.
[0155] (ST limit) The test glass plates were 15 mm square and 0.7 mm thick with a mirror-finished surface, and were chemically strengthened under various conditions to prepare multiple test glass plates with different ST values. Using a Vickers testing machine, a diamond indenter with a 90° tip angle was struck into the center of the test glass plate to break it, and the number of broken pieces was recorded as the number of broken pieces. The test was started with a diamond indenter striking load of 1 kgf, and if the glass plate did not break, the striking load was increased by 1 kgf each time, and the test was repeated until the glass plate broke, and the number of broken pieces at the first break was counted. The number of fractures was plotted against the ST value of the test glass plate, and the ST value at which the number of fractures reached 10 was read off and taken as the ST limit.
[0156] [Table 3]
[0157] [Table 4]
[0158] In Tables 3 and 4, Examples 5 and 6 have different heat treatment conditions for G5, and Examples 7 and 8 have different heat treatment conditions for G6. Comparisons between Examples 5 and 6, and between Examples 7 and 8, show that the crystallized glass of the present invention has the same composition, but the crystals precipitated change when the heat treatment temperature is changed, resulting in different hazes. The crystallized glass of the present invention has small haze and excellent transparency due to the precipitation of Li3PO4 or Li4SiO4.
[0159] <Chemical strengthening treatment and evaluation of strengthened glass> The crystallized glasses of Examples 4 and 14 were chemically strengthened by the following method, and were named Examples 15 and 16, respectively. Examples 15 and 16 are examples. A molten salt containing 0.3 mass% lithium nitrate and 99.7 mass% sodium nitrate was used as the strengthening salt, and the molten salt was held at 450°C for 30 minutes to perform an ion exchange treatment, thereby obtaining chemically strengthened glass. The stress profile of the obtained chemically strengthened glass was measured using a scattered light photoelastic stress meter SLP-2000 manufactured by Orihara Seisakusho. The results are shown in Table 5. In Table 5, the crystallized glass of glass G4 is shown as GC4, and the crystallized glass of glass G14 is shown as GC14. FIG. 2 shows the stress profile of chemically strengthened glass S1 obtained by chemically strengthening the crystallized glass of Example 4.
[0160] [Table 5]
[0161] As shown in Table 5, the chemically strengthened glass of the present invention is excellent in transparency and strength.
[0162] [Experimental Example 2] <Preparation and evaluation of amorphous glass> In the same manner as in Experimental Example 1, amorphous glasses having glass compositions shown in Table 6 in terms of oxide-based mole percent were prepared and their properties were evaluated. The fracture toughness value K1c was evaluated by the following method. The results are shown in Table 6.
[0163] (Fracture toughness value K1c) The fracture toughness value K1c (unit: MPa m) was measured by the DCDC method. 1 / 2 ) was measured by the DCDC method using a sample having the shape shown in FIG. 4 and a Shimadzu autograph AGS-X5KN, with reference to the method described in MY He, MR Turner and AG Evans, Acta Metall. Mater. 43 (1995) 3453. The stress intensity factor K1 (unit: MPa m) was measured as shown in FIG. 5. 1 / 2The K1-v curve, which shows the relationship between the stress intensity factor K1 at 0.1 m / s and the crack propagation velocity v (unit: m / s), was measured, and the obtained Region III data was regressed and extrapolated using a linear equation, and the stress intensity factor K1 at 0.1 m / s was determined as the fracture toughness value K1c.
[0164] [Table 6]
[0165] <Crystallization treatment and evaluation of crystallized glass> Crystallized glass was obtained in the same manner as in Experimental Example 1, and its properties were evaluated, except that X-ray diffraction was evaluated under the following conditions.
[0166] (X-ray diffraction: precipitated crystals) Powder X-ray diffraction was measured under the following conditions to identify the precipitated crystals. Measurement equipment: Rigaku Smart Lab X-ray used: CuKα ray Measurement range: 2θ=10°~80° Speed: 10° / min Step: 0.02°
[0167] The results are shown in Table 7. In Table 7, Examples 18 to 27 are working examples, and Example 17 is a comparative example.
[0168] [Table 7]
[0169] As shown in Table 7, the glass of the present invention had a small haze value and excellent transparency.
[0170] The chemical resistance of Example 2 in Table 3 and Example 21 in Table 7 was evaluated. After immersion in HCl with pH 1 at room temperature for 1 minute, it was immersed in NaOH with pH 12.5 at 65°C for 6 minutes. After that, the haze and transmittance were measured, and it was found that the haze of Example 2 increased to 0.73% and the transmittance at 550 nm decreased by 4.8%. On the other hand, it was found that the haze of Example 21 hardly changed at 0.03%, and the transmittance at 550 nm also decreased by only 0.7%. It can be seen that Example 21, in which Li3PO4 crystals are precipitated, has better chemical resistance than Example 2, in which Li2SiO3 crystals are precipitated.
[0171] [Experimental Example 3] Preparation and evaluation of amorphous glass In the same manner as in Example 1, amorphous glass having the glass composition shown in Table 8 in mole percent based on oxides was prepared and its properties were evaluated. However, the amounts of SO3, Cl, and SnO2 added as fining agents are shown in mass percent. The results are shown in Table 8.
[0172] [Table 8]
[0173] <Crystallization Treatment and Evaluation of Crystallized Glass> Crystallized glass was obtained and its properties were evaluated in the same manner as in Example 1. The results are shown in Table 9. In Table 9, Examples 28 to 33 are all examples.
[0174] [Table 9]
[0175] As shown in Table 9, the optical and mechanical properties of the glass of the present invention are not affected by the addition of the fining agents SO3, Cl, and SnO2, either alone or in combination.
[0176] The polishing rates of the amorphous glass and the glass of the invention are shown in Table 10. Example 34 is a comparative example, and Examples 4 and 21 are working examples.
[0177] [Table 10]
[0178] As shown in Table 10, the polishing rate of the glass of the present invention after crystallization is greater than that of general amorphous glass, and it is clear that the glass has excellent processability.
[0179] Figure 3 is a cross-sectional FE-SEM image of Example 21. In Figure 3, an example of precipitated crystals is indicated by a white arrow. The size of the precipitated crystals was measured under the following conditions and found to be 20-50 nm. Because the crystal size is small, it is less susceptible to scattering and has excellent optical properties. Apparatus: Measurement was performed using a JEOL JSM-7800F Prime. Measurement conditions: Vacc: 5kV, Coating: W, UED image
[0180] In the Rietveld analysis, the precipitated crystals were identified as Li 6.5 In the case of (Si,P)O8, the crystallinity was 18.2% and the crystallite size was 15 nm.
[0181] Although the present invention has been described in detail with reference to specific embodiments, it is apparent to those skilled in the art that various changes and modifications can be made without departing from the spirit and scope of the present invention. This application is based on a Japanese patent application (Patent Application No. 2020-140347) filed on August 21, 2020 and a Japanese patent application (Patent Application No. 2021-090475) filed on May 28, 2021, which are incorporated by reference in their entirety. In addition, all references cited herein are incorporated in their entirety.
Claims
1. In mole percent based on oxide, SiO 2 54 to 64 percent, Al 2 O 3 を3~8%、 P 2 O 5 0.5 to 4.2%, MgO: 4-7% Li 2 Oを18~26%、 Na 2 Oを1~2.5%、 ZrO 2 1 to 3.5%, Y 2 O 3 を0~4%、 B 2 O 3 0 to 10%; Contains 0 to 1.5% CeO 2 , Young's modulus is 90 to 110 GPa; The average thermal expansion coefficient at 50 to 350°C is 80 x 10 -7 / ℃ or more 110 x 10 -7 / °C or less.
2. In terms of oxide mol%, (Al 2 O 3 / LiO 2 2. The glass substrate according to claim 1, wherein NWF is SiO. 2 , Al 2 O 3 , P 2 O 5 and B 2 O 3 Represents the total amount of.
3. The glass substrate according to claim 1, containing 20% or more Li 2 O, expressed in mole percent on an oxide basis.
4. The glass substrate according to claim 1, containing 2% or more of ZrO 2 in mole percent based on the oxide.
5. The glass substrate according to claim 1, containing 1% or more of P 2 O 5 , expressed in mole percent on an oxide basis.
6. The glass substrate according to claim 1, wherein NWF (SiO 2 +Al 2 O 3 +P 2 O 5 +B 2 O 3 ) is 65% or more and 70% or less in mole percentage based on oxides.
7. A semiconductor support substrate comprising the glass substrate according to any one of claims 1 to 6.
8. Through the bonding layer, Multiple semiconductor chips are installed, Semiconductor chips molded in resin. A support substrate for a fan-out type package, comprising the glass substrate according to any one of claims 1 to 6.
Citation Information
Patent Citations
Glass ceramics and multi-layered inorganic membrane filter
CN104926135A
Substrate for information recording medium, information recording medium, and its manufacturing method
JP2004288228A
Crystallized glass
JP2010001201A
Physically-strengthened glass, and production method thereof
JP2015086080A
Chemically strengthened glass and production method therefor
WO2019022035A1
